Isolation of Cellulolytic Bacteria from the Peat Protected Forest Area in Sungai Buluh, East Tanjung Jabung Jambi - Fitratul Aini; Hesti Riany; Hasnaul Maritsa (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2022)
One of the largest composition in peatlands is Cellulose. It can be degraded by cellulase enzymes. Sungai Buluh Peatland is one of the large and protected peatlands in Jambi Province. This land can be the main habitat for cellulolytic bacteria. Peatlands cellulolytic bacteria have great potential as biocontrol agents for plant pathogenic fungi. This study aimed to obtain cellulolytic soil bacteria from Sungai Buluh Tanjung Jabung Peat Protection Forest, in the East Tanjung Jabung, Jambi, which causes stem rot disease of oil palms. This research was carried out in several stages. Firstly, soil samples were collected from the Sungai Buluh Protected Forest, East Tanjung Jabung Jambi. Then the bacteria were selected on Carboxy Methyl Cellulose (CMC) selective media and the quantitative cellulolytic activities were measured based on clear zones that formed on CMC media. The results showed that 25 isolates of cellulolytic potential bacteria were obtained from the Sungai Buluh Peat Protected Forest area, 8 of them had cellulolytic activity range from 0.87 to 6.70